Heat Transfer Enhancement with Nanofluids for Automotive Cooling - Adnun , M. Hussein; K., Kadirgama; D., Rarnasarny; R. A., Bakar (Springer, 2017)
The increasing demand of nanofluids for the industrial applications has lead to focus on it from many researchers in the last decade. This thesis includes both experimental study and numerical study to improve heat transfer with slightly pressure drop in the automotive cooling system. The friction factor and heat transferenhancement using different types of nanofluids are studied.